Squamous Cell Carcinoma of the Lung with Metastasis to the GI Tract Associated with EGFR Exon 19 Deletion - Glen J. Weiss; Agnes K. Liman; Jeffrey Allen; Philip Y. Cheung; Rajesh N. Kukunoor (Case Reports in Medicine)
We describe three confirmed cases of squamous cell carcinoma (SCC) of the lung with metastasis to the gastrointestinal (GI) tract, with two having epidermal growth factor receptor (EGFR) exon 19 deletions in all available specimens. One of these patients received EGFR tyrosine kinase directed therapy for a brief period with some symptom relief. Consideration of EGFR exon 19 mutation testing in SCC of the lung, particularly for those with GI tract metastasis, may identify this potentially drug-targetable entity.